Waqf and The Theory of Planned Behavior: A Meta-Analysis Review - Siti Nor Amira Mohamad; Muhamad Hasif Yahaya; Noor Aznaim Abd Latib; Amal Hayati Ishak; Siti Sarah Izham; Nurul Adilah Hasbullah (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 7, 2023 (Page: 1 – 18)